Towards Chinese text and DNA shift encoding scheme based on biomass plasmid storage - Yang, Xu; Lai, Langwen; Qiang, Xiaoli; Deng, Ming; Xie, Yuhao; Shi, Xiaolong; Kou, Zheng (Frontiers in Bioinformatics, 2023)
DNA, as the storage medium in organisms, can address the shortcomings of existing electromagnetic storage media, such as low information density, high maintenance power consumption, and short storage time. Current research on DNA storage mainly focuses on designing corresponding encoders to convert binary data into DNA base data that meets biological constraints. We have created a new Chinese character code table that enables exceptionally high information storage density for storing Chinese characters (compared to traditional UTF-8 encoding). To meet biological constraints, we have devised a DNA shift coding scheme with low algorithmic complexity, which can encode any strand of DNA even has excessively long homopolymer. The designed DNA sequence will be stored in a double-stranded plasmid of 744bp, ensuring high reliability during storage. Additionally, the plasmid 's resistance to environmental interference ensuring long-term stable information storage. Moreover, it can be replicated at a lower cost.